Efektivitas Minum Air Hangat dan Batuk Efektif terhadap Bersihan Jalan Napas Pasien Tuberkulosis Paru - Armelia Sri Diah Safitri; Safruddin, Safruddin; Ernasari, Ernasari (Window of Nursing Journal, 2023)
Pulmonary Tuberculosis is a disease caused by the bacterium Mycobacterium tuberculosis. The main problem that is often experienced by pulmonary tuberculosis patients is the accumulation of sputum which results in ineffective airway clearance. To overcome the ineffectiveness of airway clearance, it can be done by providing therapy with drinking warm water and effective coughing. This study aims to determine the comparison between drinking warm therapy and coughing effectively on airway clearance of pulmonary tuberculosis patients at the Bontomarannu Health Center. This research is a quantitative study using a quasi-experimental design where the researcher uses a two group pretest-posttest design. The determination of the sample is done by simple random sampling technique with a sample size of 42 respondents. This study used the Mann Withney test and the Wilcoxon test. From the results of research that has been carried out, it was found that drinking warm water therapy was effective on airway clearance (p=0.027) and cough therapy was effective on ineffective airway clearance (p=0.003). Based on the results of the study, it was shown that cough therapy was more effective in clearing the airway than drinking warm water therapy. It is suggested that this research can be used as a reference to develop knowledge regarding the handling of clearing the airway using the therapy of drinking warm water and coughing effectively